Exploring Learning Strategies and Habit Formation in Developing English-Speaking Fluency: A Narrative Inquiry - Tiarannisa Putri Lestari; Julianthi Zefana Silitonga; Ayonia Jelita Boru Sinaga; Erma Sujiyani; Muhammad Subhan Fikri (FOSTER: Journal of English Language Teaching, 2026)
English-speaking fluency is a critical competence for academic, professional, and interpersonal success, yet many learners encounter persistent linguistic, affective, and social barriers. This study employed a qualitative narrative inquiry to examine the learning strategies and habits formation of a highly proficient Indonesian EFL learner, selected through purposive sampling based on her achievements in debate and public speaking. Data were collected through semi-structured interviews and analyzed using Miles et al.’s (2014) iterative model. The findings revealed four deliberate strategies, self-talk, overcoming fear of mistakes, social interaction, and self-monitoring, that collectively enhanced confidence, resilience, and sustained oral practice. In parallel, two major dimensions of habits formation, early exposure to English through parental support and media input, and integration of English into daily life across school, professional, and familial contexts. emerged as decisive in sustaining fluency development. Unlike prior studies that emphasize group-level outcomes, this research provides a nuanced account of an individual learner’s trajectory, demonstrating how strategies and habits formation converge to embed fluency as a lifelong practice. The study contributes to the field by enriching limited research on highly proficient Indonesian EFL learners and offering pedagogical insights into how deliberate strategy use and consistent routines can be cultivated to foster enduring fluency growth.